Evaluation of the Effects of Bio-Stimulation and Gonadotropin-Releasing Hormone on First-Service Conception Rate in Buffalo Cows - Paul, Ashit Kumar; Fakruzzaman, Md.; Alam, Md. Ashadul; Deb, Gautam Kumar; Khandoker, MAM Yahia (Journal of Buffalo Science, 2026)
This study investigated the efficacy of combining bio-stimulation and hormonal interventions to enhance the first AI conception rate (CR-FAI) in buffaloes. Under field conditions, 224 adult female buffaloes were randomly assigned (lottery method) to one of two treatment protocols. In group A, AI was conducted using a modified penis-like device (mPLD) and the application of clitoral massage (CM) for 30 seconds (AI + mPLD + CM). In group B, AI included mPLD and CM supplemented with an intramuscular injection of 500 µg of gonadotrophin-releasing hormone (GnRH) immediately post-insemination (AI + mPLD + CM + GnRH). Confounding variables, including age, parity, body condition score (BCS), and breed of the buffaloes, were recorded at the time of AI. The results demonstrated that the CR-FAI in group B (77.4%) was significantly higher than in group A (63.6%; p < 0.05). While age categories exhibited significant variation in CR-FAI (p < 0.05; χ2 = 8.80), no significant variation was found for parity, BCS, or breed. Logistic regression revealed that buffaloes at parity 1 and 2 possessed 3.6-times and 2.7-times higher odds of conception, respectively, [Wald=1.02, OR =3.61, 95% CI (0.30-43.99) and Wald =1.81, OR =2.65, 95% CI (0.64-11.0)], relative to other parity groups. Furthermore, age was highly significant and positively correlated with parity and BCS (p <0.01). In conclusion, AI integrating bio-stimulation with concurrent GnRH administration substantially enhances the conception rates in buffaloes.